Mapping an archaeological site: Interpreting portable X-ray fluorescence (pXRF) soil analysis at Boroughgate, Skelton, UK. (August 2021) - Williams, Rhys; Errickson, David; Taylor, Gillian
Highlights: Portable X-ray fluorescence provides rapid survey and mapping of soil. Elemental soil analysis identified activity areas of an archaeological excavation. pXRF soil analysis can support and enhance archaeological interpretations. Abstract: Integrating chemical soil analysis with visual inspection of an archaeological excavation may enhance our knowledge of anthropogenic activities from past populations. Elemental distribution of excavated soil from a medieval longhouse at Boroughgate, Skelton, UK was investigated. Soil was extracted from the surface of a longhouse and nearby ditch, analysed using portable X-Ray fluorescence (pXRF), and data were processed into elemental heat maps. The distribution and archaeological associations of magnesium, aluminium, phosphorus, sulphur, potassium, calcium, manganese, iron and zinc were assessed. Elemental concentrations were combined to produce a simplified summary that aided the interpretation of the site, including the delimitation of internal and external zones, clean and refuse zones, and potential animal occupation or waste areas. The application of pXRF was successful at visualising elemental distribution of an excavation to explore the anthropogenic associations through interpretation heat maps.